2012
DOI: 10.1016/j.jemermed.2011.01.020
|View full text |Cite
|
Sign up to set email alerts
|

The New Japanese Postgraduate Medical Education and Quality of Emergency Medical Care

Abstract: Japanese physicians who complete the new PGME program are likely to provide higher quality of care and have greater confidence in emergency medicine compared to those who completed the old PGME program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In the 2-year residency, residents rotate through major departments for 4−12 weeks each [9]. They also work night shifts in emergency departments approximately 4−6 days a month throughout the residency, and their clinical responsibility tends to be higher in the emergency department than in day shift rotation [10]. Near-peer teaching commonly occurs in the workplace learning environment consisting of post-graduate year 1 residents (PGY1s), postgraduate year 2 residents (PGY2s), and supervising doctors [10,11].…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2-year residency, residents rotate through major departments for 4−12 weeks each [9]. They also work night shifts in emergency departments approximately 4−6 days a month throughout the residency, and their clinical responsibility tends to be higher in the emergency department than in day shift rotation [10]. Near-peer teaching commonly occurs in the workplace learning environment consisting of post-graduate year 1 residents (PGY1s), postgraduate year 2 residents (PGY2s), and supervising doctors [10,11].…”
Section: Settingmentioning
confidence: 99%
“…They also work night shifts in emergency departments approximately 4−6 days a month throughout the residency, and their clinical responsibility tends to be higher in the emergency department than in day shift rotation [10]. Near-peer teaching commonly occurs in the workplace learning environment consisting of post-graduate year 1 residents (PGY1s), postgraduate year 2 residents (PGY2s), and supervising doctors [10,11]. PGY2s teach PGY1s, young supervising doctors teach PGY2s, and senior supervising doctors teach young supervising doctors.…”
Section: Settingmentioning
confidence: 99%
“…Objectives of this PGME are to educate residents to acquire attitudes, skills, and knowledge for providing basic clinical care. A study showed that physicians who received the current PGME program were more likely to adhere to an appropriate standard of care in emergency medicine and were more confident in caring for patients with acute illnesses, compared to those who graduated before 2004 and did not receive the current PGME …”
Section: Comparison Of Gm‐ite Scores Between Pgy‐1 and Pgy‐2mentioning
confidence: 99%
“…A study showed that physicians who received the current PGME program were more likely to adhere to an appropriate standard of care in emergency medicine and were more confident in caring for patients with acute illnesses, compared to those who graduated before 2004 and did not receive the current PGME. 4 Although the current PGME is better than the no-rotation training prior to 2004, there may be still some weaknesses of the current PGME. First, overtesting in diagnostic process is highly prevalent in Japanese hospitals, 5 This subgroup analysis showed mean score 34.9 ± 5.0 of PGY-2 was significantly higher than that 34.4 ± 4.7 of PGY-1 (Table 1).…”
mentioning
confidence: 92%
“…Previous literature has shown that education about clinical reasoning and the diagnostic process may be lacking in Japan 4 and that Japanese residents are less knowledgeable about diagnostic errors than are their American residents 5 . Additionally, since overtesting is very common in Japanese hospitals, 6 residents can order unnecessary tests without clinical reasoning 7 …”
Section: Introductionmentioning
confidence: 99%